Understanding crop domestication : responses of lettuce roots under differential phosphorus conditions - Abdul Rahman, Muhamad Faiz (2018)
Root system architecture (RSA) is a dynamic system of root network capable of adapting to changes in soil environment such as decline in soil moisture and nutrient deficiency. RSA responses to different nutrient concentration levels provide a unique system to study interactions between plants and their soil environment and the effect of different nutrient levels on root development. Wild (Lactuca serriola) and domesticated (Lactuca sativa) lettuce root systems have contrasting RSA and therefore populations developed from these two contrasting parents provide unique resources to explore root traits between cultivated and domesticated crop species.